Epidemiology of lacrosse injuries treated at the United States emergency departments between 1997 and 2015. Issue 3 (2nd July 2020) - Khodaee, Morteza; Kirk, Kayleigh; Pierpoint, Lauren A; Dixit, Sameer
ABSTRACT: Lacrosse has gained substantial popularity across age groups in the past few decades, but epidemiologic sex differences of lacrosse injuries in emergency settings have not been well described. We characterized and described lacrosse-related injuries presenting to United States Emergency Departments (US EDs) using data from the National Electronic Injury Surveillance System (NEISS). From 1997 to 2015, 7, 587 lacrosse-related injuries were treated at US EDs (national estimate of 256, 358 injuries). Males accounted for 75.5% of injuries. Average age was 16.0 ± 5.0 (range 5–71) years. Sprains/strains (25.4%), contusions/abrasions (23.9%), and fractures (18.7%) were the most common diagnoses. Females sustained a higher proportion of sprains/strains (36.0%) than males (21.9%) ( p < 0.01), while males sustained a higher proportion of fractures (injury proportion ratios [IPR]; 21.3% vs. 10.8%, p < 0.01). Similar proportions of concussions were observed (IPR; 6.1% in males, 6.2% among females). Differences in injury patterns may be secondary to differences in rules and equipment between the two sports.